Human Capital in Improving Creative Industrial Performance: A study in the Creative Industry of Batik Trusmi, Cirebon District, West Java - Sutisna MN, Deden; Haizam Mohd Saudi, Mohd (International Journal of Engineering and Technology, 2018)
The research objective was to identify the dominant factors of Human Capital, the partial and simultaneous influence of human capital and Business Performance that built the Batik creative industry in Trusmi in Cirebon, West Java. The respondents of business actors and workers in this industry sector are 10 creative industries with 10 employees each. Survey research methods, data sources are primary with questionnaires, interviews and observations as data collection tools in the object of analysis. Test data using the validity, reliability and classic assumptions test with Confirmatory Factor Analysis software. The results show that of the 20 factors analyzed, there are dominant factors of Intellectual Capital as many as 6 factors namely 1) Batik training is very helpful in working, 2) status as permanent workers are very important, 3) heredity, family as a reason for batik craftsmen, 4) batik skills obtained from education and training, 5) workers have relationships with business owners still family or family, and 6) there are requirements that must be fulfilled, while working in the batik company. Contributions from human capital both to financial and non-financial performance are in large categories. Thus, to develop the Batik creative industry in Trusmi Cirebon currently seen from the aspect of human capital determined 6 dominant factors and their contribution to the performance of the creative industry.Â Â